Vascular Smooth Muscle LRP6 Limits Arteriosclerotic Calcification in Diabetic LDLR−/− Mice by Restraining Noncanonical Wnt Signals. Issue 2 (3rd July 2015) - Cheng, Su-Li; Ramachandran, Bindu; Behrmann, Abraham; Shao, Jian-Su; Mead, Megan; Smith, Carolyn; Krchma, Karen; Bello Arredondo, Yoanna; Kovacs, Attila; Kapoor, Kapil; Brill, Laurence M.; Perera, Ranjan; et al.
Abstract : Rationale: : Wnt signaling regulates key aspects of diabetic vascular disease. Objective: : We generated SM22-Cre;LRP6(fl/fl);LDLR −/− mice to determine contributions of Wnt coreceptor low-density lipoprotein receptor–related protein 6 (LRP6) in the vascular smooth muscle lineage of male low-density lipoprotein receptor–null mice, a background susceptible to diet (high-fat diet)–induced diabetic arteriosclerosis. Methods and Results: : As compared with LRP6(fl/fl);LDLR −/− controls, SM22-Cre;LRP6(fl/fl);LDLR −/− (LRP6-VKO) siblings exhibited increased aortic calcification on high-fat diet without changes in fasting glucose, lipids, or body composition. Pulse wave velocity (index of arterial stiffness) was also increased. Vascular calcification paralleled enhanced aortic osteochondrogenic programs and circulating osteopontin (OPN), a matricellular regulator of arteriosclerosis. Survey of ligands and Frizzled (Fzd) receptor profiles in LRP6-VKO revealed upregulation of canonical and noncanonical Wnts alongside Fzd10. Fzd10 stimulated noncanonical signaling and OPN promoter activity via an upstream stimulatory factor (USF)–activated cognate inhibited by LRP6. RNA interference revealed that USF1 but not USF2 supports OPN expression in LRP6-VKO vascular smooth muscle lineage, and immunoprecipitation confirmed increased USF1 association with OPN chromatin. ML141, an antagonist of cdc42/Rac1 noncanonical signaling, inhibited USF1 activation, osteochondrogenic programs, alkaline phosphatase, and vascular smooth muscle lineage calcification. Mass spectrometry identified LRP6 binding to protein arginine methyltransferase (PRMT)-1, and nuclear asymmetrical dimethylarginine modification was increased with LRP6-VKO. RNA interference demonstrated that PRMT1 inhibits OPN and TNAP, whereas PRMT4 supports expression. USF1 complexes containing the histone H3 asymmetrically dimethylated on Arg-17 signature of PRMT4 are increased with LRP6-VKO. Jmjd6, a demethylase downregulated with LRP6 deficiency, inhibits OPN and TNAP expression, USF1: histone H3 asymmetrically dimethylated on Arg-17 complex formation, and transactivation. Conclusions: : LRP6 restrains vascular smooth muscle lineage noncanonical signals that promote osteochondrogenic differentiation, mediated in part via USF1- and arginine methylation–dependent relays. Abstract : Supplemental Digital Content is available in the text.